Belief disconfirmation versus habituation approaches to situational exposure in panic disorder with agoraphobia: a pilot study. - Salkovskis, P; Hackmann, A; Wells, A; Gelder, MG; Clark, D (2007)
Exposure therapy and cognitive behaviour therapy (CBT) are both effective in the treatment of panic disorder with agoraphobia. Cognitive theories suggest that the way in which exposure to avoided situations is implemented in either treatment may be crucial. In particular, it is suggested that clinical improvement will be greatest if opportunities for disconfirmation of feared catastrophes are maximized. In a small pilot study, 16 patients with panic disorder and (moderate or severe) agoraphobia were randomly allocated to either habituation based exposure therapy (HBET) or exposure planned as a belief disconfirmation strategy and accompanied by dropping of safety-seeking behaviours. Both treatments were brief (total of 3.25 h of exposure) and were similar in terms of expectancy of change. Patients in the CBT condition showed significantly greater improvements in self-report measures of anxiety, panic and situational avoidance. They also completed significantly more steps in a standardized behavioural walk, during which they experienced significantly less anxiety. The controlled effect sizes for CBT were substantial (range 1.7-2.7), which suggests it may be a particularly efficient way of managing therapeutic exposure to feared situations in panic disorder with agoraphobia. Further research is needed to clarify the mechanism of change involved.